Respuesta :
parentheses first: 7x-3= -21
then the -7x-21 = 126
*same signs=positive answer
*different signs(a negative and a positive) = a negative answer
then the -7x-21 = 126
*same signs=positive answer
*different signs(a negative and a positive) = a negative answer
Answer:
x = -2.14
Explanations:
How to do -7 (7x - 3) = 126
1. Use distribution property
-7(7x) - 7(-3) = 126
-7 times 7x = -49x
-7 times -3 = 21 (Negative times Negative sign = positive sign)
-49x + 21 = 126
2. Combine the like terms
21 and 126 are like terms
-49 = 126 - 21 ( When negative sign or positive sign crosses an equal sign, the negative sign changes to positive and positive changes to negative)
-49x = 105
3. Divide
Divide via by -49
-49x/-49 = 105/-49
x = -2.14